STANDARDISASI EKSTRAK KULIT KAYU BANGKAL (Nauclea subdita (Korth.) Steud.) SEBAGAI BAHAN BAKU SEDIAAN KOSMETIKA - Mohammad Listianto Raharjo; Nazarni Rahm; Nadra Khairiah,; Rais Salim; Rufida; Budi Tri Cahyana (Jurnal Penelitian Hasil Hutan, 2021)
Bangkal bark is used as a cosmetic raw material by residents of South Kalimantan and has been proven to havegood pharmacological activity as an antibacterial and free radical scavenger. Phenolic is one of the compounds found inbangkal plants. It can be used as markers to standardize and determine the extract stability that will be developed aseffective and safe materials. This study aims to observe antibacterial and free radical scavenging active materials thatstable and safe from bangkal bark for application in pharmaceutical and cosmetic products. The extraction process useda percolation method with distilled water, then standardized according to the PPOMN reference and tested for stabilityusing the accelerated stability method with a total phenolic marker. The extract was tested for free radical scavengingactivity against DPPH, and antibacterial activity was tested against Propionibacterium acne and Staphylococcusaureus by disc paper diffusion method. The results showed that bangkal extract was stable during testing at 40°C and75% RH for 12 weeks. Total phenolic range between 7.18 ± 0.31−7.43 ± 0.21 µg/mg. Antiradical scavengingactivity showed a value of IC50 of 3,158.3 μg/ml, and antibacterial activity testing showed MIC value of the angkalextract against P. acne and S. aureus at ≥ 100,000 ppm and 100,000 ppm. Extract standardization results showedthat the bangkal wood extract met the quality standard and could be used as a raw material for cosmetic materials.